Estimation of the methane conversion in a capacitively coupled radio-frequency plasma - Lee, H; Savinov, SY; Song, HK; Na, BK (SOC CHEMICAL ENG JAPAN, 2001)
Methane decomposition was investigated experimentally with the capacitively coupled rf discharge. Glow discharge was generated from the low temperature capacitively coupled radio frequency (rf) plasma and was used for activating methane to make free radicals without catalysts. Operating variables in the experiment were reaction pressure, feed flow rate, and total input power. The gaseous reaction products were mainly hydrogen, ethane, propane and ethylene. When the input power increased, the density of hydrogen increased and the unsaturated groups of C-2 and C-3 began to form. The surface-phase polymerization reactions occurred inside the discharge tube wall. A mathematical model was derived using collision theory and diffusion effect of reaction products. From the result of the mathematical modeling, the simple mathematical relation of the methane conversion was obtained, and it was the function of specific input energy only. As the results of sensitivity analysis, the conversion of methane could be determined from the input flow rate and the electrical input power without measuring reaction temperature.
Keywords: ELECTRODELESS GLOW-DISCHARGE; ORGANIC COMPOUNDS; POLYMERIZATION; HYDROCARBONS; DECOMPOSITION; MONOMERS